Ottoman Military Formations in Algeria (1518-1587 AD) - Youssef , Elham; Saker , Walaa Ali (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This study examines the Ottoman military formations in Algeria ,which became part of the Ottoman Empire since the declaration of Khairuddin Berbreus ,followed in 1518, where the army was divided into two parts, both land and sea, first dealing with the study of the ground army by clarifying the origin of the recruits, and their military barracks and weapons .The research then presented a brief study of the Algerian navy ,which included Riasha in particular Arouj and Khairuddin Berbreus, the backbone of the maritime army controlling the fate of Algeria and the Mediterranean, given Algeria ’s strategic location, and the study of the fleet and its most famous ships, In addition to studying the sources of the Algerian navy and achievements, with an explanation of the results of the land and maritime activities on Algeria, which played a major role in the victories of the Ottoman Empire in its wars against its enemies and the consolidation of Algeria and its development.